TRANSPIRATION RATE AND WATER RELATIONS OF DURUM WHEAT CULTIVARS UNDER VARYING SOIL MOISTURE CONDITIONS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This study investigates the physiological determinants of transpiration intensity and water exchange in durum wheat cultivars grown under contrasting soil moisture conditions. Using a comparative assessment across moisture regimes, we analyzed cultivar-specific responses in transpiration activity and indicators of plant water status. The results show pronounced genotypic differences: transpiration and water-exchange traits varied with both soil moisture level and inherent biological characteristics of the cultivars. Drought-tolerant cultivars maintained a more stable water balance and moderated transpiration under reduced moisture, indicating adaptive regulation of water use. These findings provide a basis for selecting durum wheat with improved water-use efficiency and for optimizing irrigation strategies in water-limited environments.